Magnetic particles and their manufacturing method

Magnetic particles with a crosslinked inorganic and polymer coating address issues of iron elution and sensitivity in immunoassays, offering enhanced acid resistance, dispersibility, and specific surface area for improved assay performance.

JP7647256B2Active Publication Date: 2025-03-18TOSOH CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021064395
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-05
Publication Date
2025-03-18
Estimated Expiration
2041-04-05

AI Technical Summary

Technical Problem

Existing magnetic particles used in immunoassays suffer from iron elution in acidic solutions, reduced sensitivity due to non-specific adsorption, and poor dispersibility in water, limiting their effectiveness.

Method used

The development of magnetic particles with a core structure coated with a crosslinked inorganic layer containing nanomagnetic material and a polymer layer with long-chain alkyl groups, enhancing acid resistance, reducing iron elution, and improving dispersibility and specific surface area.

Benefits of technology

The magnetic particles exhibit excellent acid resistance, minimal iron elution, improved water dispersibility, reduced non-specific adsorption, and a large specific surface area, leading to high sensitivity in immunoassays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647256000002
    Figure 0007647256000002
  • Figure 0007647256000001
    Figure 0007647256000001
Patent Text Reader

Abstract

To provide magnetic particles excellent in acid resistance, hardly causing elution of iron even when treated with an acidic aqueous solution, having good dispersibility in water, causing little loss due to adhesion to a container, having small non-specific adsorption, having large specific surface area of particles and large amount of physiologically active substance loaded, and achieving high sensitivity of immunoassay.SOLUTION: Magnetic particles have a core particle, a first coating layer formed on a surface of the core particle, and a second coating layer formed on a surface of the first coating layer. The first coating layer is a crosslinked inorganic material layer containing a nano-magnetic material. The second coating layer is a polymer layer having a long chain alkyl group-containing structural unit having five to twenty carbon atoms.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to magnetic particles used in immunoassays and a method for producing the same. [Background technology]

[0002] Magnetic particles are used as carriers for carrying physiologically active substances for immunoassays, taking advantage of their magnetic properties. However, when binding physiologically active substances such as antibodies to the surface of magnetic particles, the reaction is carried out in an acidic aqueous solution, which causes problems such as the detachment of magnetic bodies and the elution of iron ions, which are derived from magnetic body components. Since iron acts as an interfering substance in immune reactions, there are problems such as a decrease in sensitivity of immune assays and a limitation in the number of physiologically active substances that can be sensitized, and magnetic particles with less leakage of such magnetic body components are desired. In addition, magnetic particles as carriers for immune assays are required to have low noise by suppressing nonspecific adsorption of components unrelated to immune reactions, and high signaling that allows many physiologically active substances to be carried, thereby enabling high sensitivity in immune assays. Furthermore, since magnetic particles are dispersed in an aqueous solution for use in immune assays, magnetic particles with good dispersibility in water are required.

[0003] To solve these problems, particles for immunoassays have been proposed in which the surface of a magnetic particle having a ferrite coating layer on the surface of the core particle is coated with an organic silane coupling agent having a functional group such as an amino group, and a carboxyl group is further introduced (see, for example, Patent Document 1). Also, particles for immunoassays have been proposed in which a nanomagnetic material coated with a hydrophobic organic silane coupling agent is adsorbed onto a core particle, and then the nanomagnetic material is coated with a hydrophobic polymer so that it is embedded, and a functional group is further introduced onto the surface (see, for example, Patent Document 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 2979414 [Patent Document 2] Patent No. 3738847 Summary of the Invention [Problem to be solved by the invention]

[0005] In Patent Document 1, although the elution of iron can be suppressed by treating the surface with an organic silane coupling agent, there is a problem in that the suppression is insufficient.

[0006] In Patent Document 2, the elution of iron is suppressed by forming a hydrophobic polymer layer after coating the surface of a core particle with a magnetic material treated with a hydrophobic organic silane coupling agent, but there is a problem that the hydrophobic polymer layer deteriorates the dispersibility of the magnetic particles in water. In addition, since the nanomagnetic material is buried in the polymer by coating with a hydrophobic polymer layer, the specific surface area of ​​the magnetic particles is small, and a large amount of magnetic particles is required to support the desired amount of a physiologically active substance such as an antibody.

[0007] The present invention has been made in consideration of the above-mentioned problems, and aims to provide magnetic particles that have excellent acid resistance, cause little iron leaching even when treated with an acidic aqueous solution, have good dispersibility in water, have little loss due to adhesion to containers, and have little non-specific adsorption, as well as a large specific surface area for carrying a large amount of physiologically active substances, enabling high sensitivity in immunoassays. [Means for solving the problem]

[0008] As a result of extensive research in light of the above, the inventors have discovered that the above problems can be solved by the following magnetic particles and method for producing magnetic particles, thereby completing the present invention.

[0009] The various aspects of the present invention are as follows [1] to

[11] . [1] A magnetic particle having a core particle, a first coating layer formed on the surface of the core particle, and a second coating layer formed on the surface of the first coating layer, the first coating layer is a crosslinked inorganic layer containing nanomagnetic material; The magnetic particles, wherein the second coating layer is a polymer layer having a structural unit containing a long-chain alkyl group having 5 to 20 carbon atoms. [2] The magnetic particle described in [1], characterized in that the first coating layer has at least two layers: a nanomagnetic layer and a crosslinked inorganic layer formed on the surface of the nanomagnetic layer. [3] The magnetic particle according to [1] or [2], wherein the long-chain alkyl group-containing structural unit has a sulfonic acid group. [4] The magnetic particle according to any one of [1] to [3], wherein the long-chain alkyl group-containing structural unit has a polyethylene glycol group. [5] The magnetic particle according to any one of [1] to [4], wherein the polymer has a monomer unit having a hydrophobic group having 1 to 20 carbon atoms on a side chain. [6] The magnetic particle according to any one of [1] to [5], wherein the polymer has a monomer unit having a carboxyl group on the side chain. [7] The magnetic particle according to any one of [1] to [6], wherein the crosslinked inorganic layer of the first coating layer contains silica. [8] Specific surface area is 2 to 100 m 2 / g. [9] A method for producing magnetic particles according to any one of [1] to [8], comprising the following steps (i) to (iii): (i) A step of physically adsorbing a nanomagnetic material onto the surface of a core particle (ii) forming a cross-linked inorganic layer on the surface of the particles to which the nanomagnetic material is adsorbed; (iii) A step of dispersing the particles having the crosslinked inorganic layer formed thereon in an aqueous solution, and forming a polymer layer on the surface of the particles by free radical polymerization of a monomer in the aqueous solution in the presence of a surfactant having a long-chain alkyl group having 5 to 20 carbon atoms.

[10] A method for producing magnetic particles according to [9], characterized in that step (i) includes a step of electrostatically adsorbing a nanomagnetic material onto a core particle in an aqueous solution, followed by drying.

[11] A method for producing magnetic particles according to [9] or

[10] , characterized in that step (i) includes a step of dispersing magnetic particles in a high-velocity air stream and dry-processing the surface by impact force between the particles. Effect of the Invention

[0010] The magnetic particles according to one embodiment of the present invention have excellent acid resistance, resulting in little iron leaching even when treated with an acidic aqueous solution, and furthermore have good dispersibility in water, little loss due to adhesion to containers, little non-specific adsorption, and the particles have a large specific surface area and can carry a large amount of physiologically active substances, enabling high sensitivity immunoassays. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic diagram showing the configuration of a magnetic particle according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment for carrying out the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. The present embodiment is an example for explaining the present invention, and is not intended to limit the present invention to the following content. The present invention can be carried out by appropriately modifying it within the scope of its purpose.

[0013] In the present invention, "immunoassay" refers to a method for measuring the concentration of a physiologically active substance (such as a protein) using an antigen-antibody reaction. A carrier carrying a physiologically active substance such as an antibody or antigen is used, and the antigen-antibody reaction is allowed to proceed in a container, and finally visualized by an enzyme reaction. The concentration of an antigen contained in a sample of unknown concentration can be measured by back-calculating from a calibration curve obtained by measuring an antigen of known concentration. Immunoassay methods include the sandwich method and the competitive method.

[0014] The sandwich method uses two types of antibodies or antigens. An example of the measurement principle of the sandwich method is as follows. After the antigen in the sample is sandwiched between the first antibody immobilized on a solid phase and the second antibody labeled with an enzyme, unreacted components are removed by washing. If a substrate that emits light through an enzyme reaction is added, a signal corresponding to the antigen concentration is obtained. The more antigen there is in the sample components, the more the amount of reaction with the labeled antibody increases, and the higher the signal becomes.

[0015] The competitive method is often used when detecting small molecules that cannot have multiple epitopes. An example of the measurement principle of the competitive method is as follows.

[0016] A sample containing an antigen that reacts with the solid-phase antibody and an enzyme-labeled antigen that reacts with the solid-phase antibody are added to the antibody immobilized on the solid phase, causing a competitive reaction between the unlabeled and labeled antigens. If the unreactive material is removed by washing and a substrate that emits light through an enzyme reaction is added, a signal corresponding to the antigen concentration can be obtained. The more antigen there is in the sample components, the less the amount of reaction with the labeled antigen will decrease, resulting in a lower signal.

[0017] The magnetic particles according to one aspect of the present invention are A magnetic particle having a core particle, a first coating layer formed on a surface of the core particle, and a second coating layer formed on a surface of the first coating layer, the first coating layer is a crosslinked inorganic layer containing nanomagnetic material; The magnetic particles are characterized in that the second coating layer is a polymer layer having a structural unit containing a long-chain alkyl group having 5 to 20 carbon atoms.

[0018] The core particle used in the magnetic particle is a particle located at the very center of the magnetic particle, and there is no particular limitation on the shape or material of the core particle. The shape of the core particle can be appropriately selected, and examples thereof include a spherical shape close to a perfect sphere, a non-spherical shape such as an ellipsoid, a cube, a cylinder, or a polygonal column, and a particle having a large specific surface area and irregularities such as a porous shape or a particle having protrusions. Since it is suitable for coating many nanomagnetic bodies on the surface of the core particle, a particle having a large specific surface area and irregularities such as a porous shape or a particle having protrusions is preferred.

[0019] In order to obtain magnetic particles with good magnetic response, the particle diameter of the core particles is preferably 0.1 μm or more, more preferably 0.5 μm or more, particularly preferably 1 μm or more, and most preferably 2 μm or more. In order to obtain magnetic particles with good redispersibility in water, the particle diameter of the core particles is preferably 100 μm or less, more preferably 10 μm or less, particularly preferably 5 μm or less, and most preferably 3 μm or less.

[0020] Examples of the material of the core particle include organic compounds such as polymers, inorganic compounds, etc. Examples of the material that can be appropriately selected from these include polymer particles containing styrene-based monomer units, acrylate-based monomer units, or methacrylate-based monomer units, and silica particles.

[0021] Examples of the styrene-based monomer include styrene, α-methylstyrene, vinyltoluene, p-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-ethylstyrene, 4-tert-butylstyrene, 3,4-dimethylstyrene, 4-methoxystyrene, 4-ethoxystyrene, 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, 2,4-dichlorostyrene, 2,6-dichlorostyrene, 4-chloro-3-methylstyrene, divinylbenzene, and sodium p-styrenesulfonate.

[0022] Examples of the acrylate monomer or methacrylate monomer include (cyclo)alkyl (meth)acrylates such as (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and cyclohexyl (meth)acrylate; alkoxy (cyclo)alkyl (meth)acrylates such as 2-methoxyethyl (meth)acrylate and p-methoxycyclohexyl (meth)acrylate; (meth)acrylates; polyvalent (meth)acrylates such as trimethylolpropane tri(meth)acrylate; vinyl esters such as vinyl acetate, vinyl propionate, and vinyl versatate; cyanoacrylates such as 2-cyanoethyl (meth)acrylate, 2-cyanopropyl (meth)acrylate, and 3-cyanopropyl (meth)acrylate; hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxypropyl (meth)acrylate, and 5-hydroxypropyl (meth)acrylate; Examples of the polymer particles include polymer particles having (meth)acrylate as a monomer unit, such as substituted hydroxy (meth)acrylates, such as cyclohexyl (meth)acrylate, neopentyl glycol mono (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 3-amino-2-hydroxypropyl (meth)acrylate, etc.; glycidyl group-containing acrylates, such as glycidyl (meth)acrylate, methyl glycidyl methyl acrylate, epoxidized cyclohexyl (meth)acrylate, etc.; and polyfunctional (meth)acrylates, such as trimethylolpropane ethoxy triacrylate, pentaerythritol ethoxy tetraacrylate, trimethylolpropane propoxy triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol hexaacrylate, polyethylene glycol diacrylate, polypropylene glycol diacrylate, tricyclodecane dimethanol diacrylate, ethoxylated phenyl acrylate, etc. The (meth)acrylate may be crosslinked.

[0023] If necessary, the core particles may contain a nanomagnetic material. In addition, a paramagnetic thin film coating layer may be provided on the surface of the core particles. When a paramagnetic coating layer is provided, it is preferable for the thickness to be 0.001 to 1 μm, more preferably 0.001 to 0.1 μm, particularly preferably 0.001 to 0.01 μm, and most preferably 0.001 to 0.005 μm, since it is suitable for reducing residual magnetization of the particles and suppressing aggregation between the particles.

[0024] In addition, as a pretreatment for providing the first coating layer, the surface of the core particle may be coated with a substance having a positive or negative charge. There is no particular limitation on the method for coating the surface of the core particle with a substance having a positive or negative charge, but examples of the method include a method of forming a polymer layer on the surface of the core particle using a monomer having a charge on its side chain, and a method of coating the surface of the core particle with a charged polymer by a layer-by-layer method.

[0025] The first coating layer formed on the surface of the core particle is a crosslinked inorganic layer containing a nanomagnetic material. The nanomagnetic material is a particle having a smaller particle diameter than the core particle, and further has magnetic responsiveness. Since it is preferable that the nanomagnetic material has superparamagnetism, the particle diameter of the nanomagnetic material is preferably 0.001 to 1 μm, more preferably 0.001 to 0.5 μm, particularly preferably 0.001 to 0.1 μm, and most preferably 0.001 to 0.05 μm. Examples of the material include iron oxide such as magnetite.

[0026] The nanomagnetic material may contain an inorganic surface modifier such as a lipid or a silane coupling agent on the surface. Examples of the silane coupling agent include vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, tris-(trimethoxysilylpropyl)isocyanurate, 3-ureidopropyltrialkoxysilane, 3-mercaptopropylmethyldimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, and 3-isocyanatepropyltriethoxysilane.

[0027] It is preferred that the nanomagnetic particles are dispersed in the crosslinked inorganic layer, or that the surface of the nanomagnetic particles is completely covered with the crosslinked inorganic layer. By dispersing the nanomagnetic particles in the crosslinked inorganic layer, or by completely covering the surface of the nanomagnetic particles with the crosslinked inorganic layer, the acid resistance of the magnetic particles can be increased.

[0028] The content of the nanomagnetic material is preferably 0.1 g / g or more, more preferably 0.2 g / g or more, particularly preferably 0.5 g / g or more, and most preferably 0.7 g / g or more per 1 g of magnetic particles, since it is suitable for making magnetic particles with good magnetic response. Also, since it is suitable for increasing the dispersibility of the magnetic particles in water, the content of the nanomagnetic material is preferably 0.9 g / g or less, more preferably 0.8 g / g or less, particularly preferably 0.7 g / g or less, and most preferably 0.6 g / g or less per 1 g of magnetic particles.

[0029] Furthermore, for the purpose of controlling the specific gravity of the particles for immunoassay and adjusting the sedimentation rate of the particles, the weight proportion of the nanomagnetic material contained in the magnetic particles is preferably 5 to 70 wt%, more preferably 10 to 60 wt%, particularly preferably 15 to 50 wt%, and most preferably 20 to 40 wt%.

[0030] The crosslinked inorganic layer is formed by coating the surface of the core particle with a crosslinked inorganic material. Examples of the crosslinked inorganic material include silica, glass, oxides such as magnesium oxide and alumina oxide, and ceramics such as zirconia and hydroxyapatite. Among these, silica is preferred because it is particularly suitable for increasing acid resistance. By providing a crosslinked inorganic layer, it is possible to increase acid resistance while being hydrophilic, and therefore it is possible to impart the contradictory properties of suppressing iron elution and dispersing the particles in water. In addition, the crosslinked inorganic layer is coated along the shape of the magnetic material on the particle surface and does not completely bury the magnetic material, so that a magnetic particle with a large specific surface area can be obtained, and the amount of biologically active substances such as antibodies carried can be increased. The thickness of the crosslinked inorganic layer is preferably 0.001 μm or more, more preferably 0.005 μm or more, particularly preferably 0.01 μm or more, and most preferably 0.05 μm or more, because it is suitable for increasing acid resistance. In order to obtain magnetic particles with a large specific surface area, the thickness of the crosslinked inorganic layer is preferably 0.1 μm or less, more preferably 0.05 μm or less, particularly preferably 0.02 μm or less, and most preferably 0.01 μm or less.

[0031] Furthermore, for the purpose of controlling the specific gravity of the particles for immunoassay and adjusting the sedimentation rate of the particles, the content of the crosslinked inorganic material contained in the magnetic particles is preferably 0.1 to 10 wt%, more preferably 0.5 to 5 wt%, particularly preferably 1 to 5 wt%, and most preferably 1 to 3 wt%.

[0032] The method for forming the crosslinked inorganic layer containing the nanomagnetic material is not particularly limited, and examples thereof include a method in which the nanomagnetic material is adsorbed and accumulated on the surface of the core particle, and then a crosslinked inorganic layer is formed, a method in which the nanomagnetic material is added when forming the crosslinked inorganic layer, etc. The method in which the nanomagnetic material is adsorbed and accumulated on the surface of the core particle, and then a crosslinked inorganic layer is formed is preferred because the reaction can be easily controlled.

[0033] Examples of the method for adsorbing the nanomagnetic material on the surface of the core particle include a method in which the core particle and a nanomagnetic material having a surface charge opposite to that of the core particle are mixed in an aqueous solution, and the nanomagnetic material is spontaneously adsorbed on the surface of the core particle by electrostatic interaction, a method in which the nanomagnetic material is bonded to the surface of the core particle by a chemical reaction between the functional group on the surface of the core particle and the nanomagnetic material, and a method in which the core particle and the nanomagnetic material are combined by applying mechanical energy. The method for adsorbing the nanomagnetic material on the surface of the core particle may be a combination of a plurality of methods, and for example, the nanomagnetic material may be spontaneously adsorbed on the surface of the core particle by electrostatic interaction, and then the dried particles may be used, and mechanical energy may be applied to firmly adsorb the nanomagnetic material to the core particle.

[0034] As a method for spontaneously adsorbing the nanomagnetic material to the core particle surface by the electrostatic interaction, it is preferable to mix the core particle and the nanomagnetic material in an aqueous solution, which is suitable for increasing the amount of the nanomagnetic material adsorbed to the core particle, and an aqueous solution containing an electrolyte such as sodium chloride is more preferable. In the case of an aqueous solution containing an electrolyte, the electrolyte concentration is preferably such that the nanomagnetic material does not aggregate with each other, and for example, a concentration of about 0.01 to 0.5 M can be suitably used. In addition, in order to firmly fix the adsorbed nanomagnetic material to the core particle surface, it is preferable to dry the particles after compounding in the aqueous solution.

[0035] The method of compounding the core particles and the nanomagnetic material by applying mechanical energy is preferably a method capable of treating particles in a dry manner, such as a device for compounding by swirling force in a high-speed air stream, a device for mixing and stirring using a rotation-revolution mixer or a ball mill, a device for surface coating using a spray dryer, etc. Examples of the device include the Hybridization System NHS Series (manufactured by Nara Machinery Works, Ltd.), Nobilta NOB (manufactured by Hosokawa Micron Corporation), High-Speed ​​Mixing Type Powder Spheroidizer NSM Series (manufactured by Seishin Enterprise Co., Ltd.), and Mini Spray Dryer B-290 Type (Shibata Scientific Co., Ltd.).

[0036] When the compounding is performed by the rotational force in the high-speed airflow, the rotation speed is set to 8000 min-1, which is suitable for firmly fixing the magnetic material to the core particles. -1 More than 9000min is preferable. -1 More preferably, 10,000 min -1 More than 11000min is especially preferable. -1 The above is the most preferable. In addition, a rotation speed of 15,000 min−1 is preferable because it is suitable for forming the particle shape into a spherical shape. -1 Less than 14000min is preferable. -1 Less than 13000min is more preferable. -1 The following is particularly preferred: 12000min -1 The treatment time is preferably 1 to 60 minutes, more preferably 1 to 20 minutes, particularly preferably 1 to 10 minutes, and most preferably 3 to 10 minutes, because it is suitable for forming the particle shape into a spherical shape. The treatment temperature is preferably 25 to 80°C, more preferably 25 to 60°C, particularly preferably 25 to 50°C, and most preferably 25 to 40°C, because it is suitable for suppressing fusion of the particles.

[0037] When silica is formed as a crosslinked inorganic substance, a method of dispersing particles in a solvent and then adding tetraethyl orthosilicate and aqueous ammonia can be suitably used. The amount of tetraethyl orthosilicate added during the reaction is preferably 0.05 g or more per 1 g of particles, more preferably 0.1 g or more, more preferably 0.2 g or more, and most preferably 0.5 g or more, because it is suitable for forming a sufficient amount of silica on the particle surface. In addition, it is preferably 5 g or less per 1 g of particles, more preferably 2 g or less, particularly preferably 1 g or less, and most preferably 0.5 g or less, because it is suitable for suppressing the aggregation of particles during the reaction. Furthermore, the amount of aqueous ammonia added during the reaction is preferably 20 mL or more per 1 L of solvent, more preferably 30 mL or more, particularly preferably 40 mL or more, and most preferably 50 mL or more, because it is suitable for forming a sufficient amount of silica on the particle surface. Furthermore, since this is suitable for suppressing aggregation of particles during the reaction, the amount is preferably 100 mL or less, more preferably 80 mL or less, particularly preferably 70 mL or less, and most preferably 60 mL or less, per 1 L of solvent.

[0038] As a reaction solvent when forming silica as a crosslinked inorganic material, ethanol, 2-propanol, and butanol are preferable, ethanol or 2-propanol are more preferable, and 2-propanol is particularly preferable, because these are suitable for uniformly coating silica while suppressing particle aggregation.

[0039] The second coating layer formed on the surface of the first coating layer is a polymer layer having a long-chain alkyl group-containing structural unit having 5 to 20 carbon atoms. Since the particle having the first coating layer formed on the surface of the core particle does not have a functional group for binding a physiologically active substance such as an antibody to the particle, it cannot support the physiologically active substance. Therefore, by providing the second coating layer on the surface of the particle provided with the crosslinked inorganic layer, it becomes possible to support the physiologically active substance while suppressing non-specific adsorption, and it is possible to increase the sensitivity of the immunoassay. By having a long-chain alkyl group-containing structural unit having 5 to 20 carbon atoms, it is possible to support many physiologically active substances by hydrophobic interaction while suppressing non-specific adsorption, and it is possible to increase the sensitivity of the immunoassay. In the case of a long-chain alkyl group-containing structural unit having less than 5 carbon atoms, the hydrophobic interaction for supporting the physiologically active substance is insufficient, and a sufficient amount of the physiologically active substance cannot be supported, so the positive count of the immunoassay decreases and the sensitivity of the immunoassay decreases. Since it is suitable for increasing the amount of physiologically active substance carried and enhancing the sensitivity of immunoassay, it is more preferable that the carbon number is 7 or more, particularly preferably that the carbon number is 9 or more, and most preferably that the carbon number is 11 or more. In addition, in the case of a long-chain alkyl group-containing structural unit having more than 20 carbon atoms, components other than the target physiologically active substance are nonspecifically adsorbed, so that the sensitivity of immunoassay decreases. Since it is suitable for enhancing the sensitivity of immunoassay, it is more preferable that the carbon number is 18 or less, particularly preferably that the carbon number is 16 or less, and most preferably that the carbon number is 14 or less.

[0040] The structural unit containing a long-chain alkyl group having 5 to 20 carbon atoms is preferably a surfactant, and any of anionic, cationic, nonionic and zwitterionic surfactants can be used.

[0041] For competitive immunoassays, it is preferable that the long-chain alkyl group-containing structural unit further has a sulfonic acid group. Examples of such salts include alkyl sulfonates such as sodium n-hexyl sulfate, sodium heptyl sulfate, sodium octyl sulfate, sodium nonyl sulfate, sodium decyl sulfate, sodium dodecyl sulfate, sodium hexadecyl sulfate, and sodium octadecyl sulfate; and alkyl benzene sulfonates such as sodium hexylbenzene sulfonate, sodium dodecylbenzene sulfonate, and sodium octadecylbenzene sulfonate.

[0042] In addition, since it is suitable for increasing the measurement sensitivity in immunoassay by the sandwich method, it is preferable that the long-chain alkyl group-containing structural unit further has a polyethylene glycol group. In the sandwich method, it is necessary to reduce non-specific adsorption of a physiologically active substance in order to increase the sensitivity, and the polyethylene glycol group works effectively. Examples of the long-chain alkyl group-containing structural unit having the polyethylene glycol group include polyoxyethylene alkyl ether, polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene myristyl ether, polyoxyethylene alkylene alkyl ether, polyoxyethylene phenyl ether, polyoxyethylene tribenzyl phenyl ether, polyoxyethylene polyoxypropylene, polyoxyethylene polyoxypropylene alkyl ether, polyethylene glycol alkyl ester, polyoxyalkylene glycol rosin acid ester, and polyoxyethylene alkylamine, and polyoxyethylene alkyl ether having a long chain alkyl of 5 to 20 carbon atoms is preferable. In addition, since it is suitable for suppressing non-specific adsorption, the molecular weight of the polyoxyethylene is preferably 500 or more, more preferably 1000 or more, more preferably 1500 or more, and particularly preferably 2000 or more. Furthermore, in order not to inhibit the carrying of a physiologically active substance, the molecular weight of the polyoxyethylene is preferably 20000 or less, more preferably 10000 or less, particularly preferably 5000 or less, and most preferably 3000 or less.

[0043] In addition, it is preferable that the long-chain alkyl group-containing structural unit is covalently bonded to a polymer. By covalently bonding the long-chain alkyl group-containing structural unit to a polymer, the particles have excellent long-term storage stability. As a method for covalently bonding the long-chain alkyl group-containing structural unit to a polymer, a method can be mentioned in which a polymerization reaction is carried out on the particle surface in the presence of a surfactant, and the radicals generated by the polymerization reaction are chain-transferred to the surfactant.

[0044] In addition, from the viewpoint of long-term storage stability of the particles, it is preferable that the polymer of the second coating layer is covalently bonded to the first coating layer. There is no particular limitation on the method of covalently bonding the polymer to the first coating layer, but for example, a method of chemically bonding a polymerization initiator or a monomer to the surface of the first coating layer using a silane coupling agent and then carrying out polymerization can be mentioned.

[0045] The polymer of the second coating layer also preferably has a monomer unit having a hydrophobic group having 1 to 20 carbon atoms in the side chain. By having a monomer unit having a hydrophobic group in the side chain, it is suitable for imparting hydrophobicity for adsorbing or binding an antibody to the particle surface. In addition, by using a monomer having a hydrophobic group in the side chain, it becomes easier to uniformly introduce a long-chain alkyl group-containing structural unit onto the magnetic particle surface. The monomer unit having a hydrophobic group in the side chain is not particularly limited, but it is preferable that the monomer unit has a long-chain and cyclic alkyl group having 1 to 20 carbon atoms in the side chain, more preferably has a long-chain and cyclic alkyl group having 1 to 10 carbon atoms in the side chain, particularly preferably has a long-chain and cyclic alkyl group having 1 to 6 carbon atoms in the side chain, and most preferably has a long-chain and cyclic alkyl group having 6 carbon atoms in the side chain. Examples of such acrylates include methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, n-butyl acrylate, n-butyl methacrylate, t-butyl acrylate, t-butyl methacrylate, n-pentanoyl acrylate, n-pentanoyl methacrylate, n-hexyltyl acrylate, n-hexyl methacrylate, cyclopropyl acrylate, cyclopropyl methacrylate, cyclohexyl acrylate, cyclohexyl methacrylate, phenyl acrylate, phenyl methacrylate, and styrene.

[0046] The polymer of the second coating layer also preferably has a monomer unit having a carboxyl group on the side chain. By having a monomer unit having a carboxyl group on the side chain, a physiologically active substance can be immobilized on the particle surface via the carboxyl group, and the sensitivity of the immunoassay can be increased. The monomer having the carboxyl group-containing structural unit is not particularly limited except that it contains a carboxyl group, and examples thereof include acrylic acid, methacrylic acid, maleic acid, and fumaric acid.

[0047] In addition, the second coating layer may contain a hydroxyl group-containing structural unit as a hydrophilic group other than polyethylene glycol, and examples of the monomer include hydroxyethyl acrylate, hydroxyethyl methacrylate, N-(2-hydroxyethyl)acrylamide, 2-hydroxyphenyl acrylate, 2-hydroxyphenyl methacrylate, 3-hydroxyphenyl acrylate, 3-hydroxyphenyl methacrylate, 4-hydroxyphenyl acrylate, and 4-hydroxyphenyl methacrylate.

[0048] The polymerization initiator used in forming the second coating layer is not particularly limited, and depending on the desired polymerization temperature and polymerization rate, azo compounds such as azobisisobutyronitrile, peroxides such as potassium peroxodisulfate, peroxyesters such as Perhexyl PV and Perbutyl O (manufactured by NOF Corporation), and the like can be suitably used.

[0049] The polymer layer, which is the second coating layer, is preferably chemically bonded to the first coating layer directly or via a linker. By being chemically bonded directly or via a linker, acid resistance and solvent resistance can be improved. The presence of chemical bonds can be confirmed by the fact that the polymer does not disappear even when washed with a solvent that dissolves the polymer. If there is no chemical bond, the coated polymer will almost entirely dissolve and disappear.

[0050] The second coating layer is fixed to the first coating layer by chemical bonding, which is suitable for enhancing the acid resistance and solvent resistance of the magnetic particles, so it is preferable that the crosslinked inorganic layer has a silane coupling agent having a polymerizable functional group (and residue) on the surface. Examples of the silane coupling agent include vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane.

[0051] When the silane coupling agent is reacted on the surface of the crosslinked inorganic layer, a method of adding the silane coupling agent and aqueous ammonia after dispersing the particles in a solvent can be suitably used. The amount of the silane coupling agent added during the reaction is preferably 0.05 g or more per 1 g of particles, more preferably 0.1 g or more, more preferably 0.2 g or more, and most preferably 0.5 g or more, because it is suitable for reacting a sufficient amount of the silane coupling agent on the particle surface. In addition, it is preferably 5 g or less per 1 g of particles, more preferably 2 g or less, particularly preferably 1 g or less, and most preferably 0.5 g or less, because it is suitable for suppressing the aggregation of particles during the reaction. Furthermore, the amount of aqueous ammonia added during the reaction is preferably 20 mL or more per 1 L of solvent, more preferably 30 mL or more, particularly preferably 40 mL or more, and most preferably 50 mL or more, because it is suitable for reacting a sufficient amount of the silane coupling agent on the particle surface. Furthermore, since this is suitable for suppressing aggregation of particles during the reaction, the amount is preferably 100 mL or less, more preferably 80 mL or less, particularly preferably 70 mL or less, and most preferably 60 mL or less, per 1 L of solvent.

[0052] As a reaction solvent for reacting the silane coupling agent, since it is suitable for reacting the silane coupling agent uniformly while suppressing particle aggregation, alcohols such as methanol, ethanol, 2-propanol, butanol, etc. are preferable, methanol, ethanol, and 2-propanol are more preferable, and methanol or 2-propanol is particularly preferable.

[0053] The amount of polymer coated in the second coating layer is not particularly limited, but since it is suitable for producing magnetic particles with a large specific surface area, the amount of polymer coated per 1 g of magnetic particles is preferably 1 g / g or less, more preferably 0.5 g / g or less, particularly preferably 0.1 g / g or less, and most preferably 0.05 g / g or less. Also, since it is suitable for improving acid resistance, the amount of polymer coated per 1 g of magnetic particles is preferably 0.001 g / g or more, more preferably 0.01 g / g or more, particularly preferably 0.1 g / g or more, and most preferably 0.5 g / g or more. The amount of polymer coated can be measured by measuring the TG-DTA of the particles before and after coating with the polymer and determining the difference in thermal weight loss before and after coating with the polymer. It can also be calculated by determining the thickness of the polymer from a scanning electron microscope image of the particle cross section or a transmission electron microscope image of the particle.

[0054] The amount of carboxyl groups in the magnetic particles is preferably 5 μmol / g or more, more preferably 10 μmol / g or more, particularly preferably 20 μmol / g or more, and most preferably 50 μmol / g or more, per 1 g of magnetic particles, since it is suitable for making the magnetic particles capable of binding many antibodies. In addition, the amount of carboxyl groups in the magnetic particles is preferably 200 μmol / g or less, more preferably 100 μmol / g or less, particularly preferably 50 μmol / g or less, and most preferably 20 μmol / g or less, per 1 g of magnetic particles, since it is suitable for suppressing non-specific adsorption of substances other than antibodies to the magnetic particles and generation of measurement noise in immunoassays. The method for measuring the amount of carboxyl groups includes a method of mixing pyrenyldiazomethane with magnetic particles and quantifying the amount of pyrenyldiazomethane lost by the reaction, or a method of directly quantifying the amount of carboxyl groups on the surface of the magnetic particles by potentiometric titration.

[0055] The magnetic particles according to one embodiment of the present invention have a specific surface area of ​​2 m 2 / g or more. 2 / g or more, the amount of antibody that can be bound to the surface of the magnetic particles per unit weight can be increased, and the signal strength in immunoassays can be increased. Therefore, a large specific surface area makes it possible to perform immunoassays with a small amount of magnetic particles. In addition, a specific surface area of ​​5 m 2 / g or more is more preferable, and 2 / g or more is particularly preferred, and 20m 2 On the other hand, a specific surface area of ​​100 m / g or more is preferable because it is suitable for increasing the mechanical strength of the magnetic particles. 2 / g or less is preferable, and 50m 2 / g or less is more preferable, and 40m 2 / g or less is particularly preferable, and 30m 2 / g or less is most preferable.

[0056] The magnetic particles according to one embodiment of the present invention can be obtained by a production method including the following steps (i) to (iii). (i) A step of physically adsorbing a nanomagnetic material onto the surface of a core particle (ii) forming a cross-linked inorganic layer on the surface of the particles to which the nanomagnetic material is adsorbed; (iii) A step of dispersing the particles having the crosslinked inorganic layer formed thereon in an aqueous solution, and forming a polymer layer on the surface of the particles by free radical polymerization of a monomer in the aqueous solution in the presence of a surfactant having a long-chain alkyl group having 5 to 20 carbon atoms. In step (i), the nanomagnetic material is physically adsorbed to the surface of the core particle by a method of contacting the nanomagnetic material having an opposite charge to the surface charge of the core particle, a method of contacting the hydrophobic nanomagnetic material with the hydrophobic core particle, or a method of contacting the nanomagnetic material with the paramagnetic core particle. The method of contacting the core particle and the nanomagnetic material is not particularly limited, and it can be done by stirring in a liquid phase or a gas phase. Since it is suitable for uniformly adsorbing the nanomagnetic material to the core particle, it is preferable to electrostatically adsorb the nanomagnetic material to the core particle in an aqueous solution. In addition, in order to firmly fix the electrostatically adsorbed nanomagnetic material, it is preferable to dry the particles after electrostatic adsorption. Furthermore, since it is suitable for making the shape of the particles spherical, it is preferable to disperse the magnetic particles in a high-speed airflow and perform surface modification in a dry manner by the impact force between the particles.

[0057] In step (ii), a crosslinked inorganic layer is formed on the surface of the particles to which the nanomagnetic material has been adsorbed in step (i). There is no particular limitation on the method for forming the crosslinked inorganic layer, but examples include a method in which the particles are dispersed in a solution containing a reagent and a reaction catalyst that are raw materials for the crosslinked inorganic layer, and a crosslinked inorganic layer is formed on the particle surface by proceeding with a reaction, and a method in which the particle surface is coated with the crosslinked inorganic layer or the raw materials thereof.

[0058] In step (iii), the particles on which the crosslinked inorganic layer is formed in step (ii) are dispersed in an aqueous solution, and a monomer is subjected to free radical polymerization in the aqueous solution in the presence of a surfactant having a long-chain alkyl group having 5 to 20 carbon atoms to form a polymer layer on the surface of the particles. Examples of the polymerization method include a dispersion polymerization method in which polymerization is performed in a state in which all components other than the particles are dissolved in a solvent, and a seed polymerization method in which polymerization is performed in a state in which a monomer incompatible with the solvent is used and the monomer is adsorbed on the particles. In addition, the seed polymerization method can be appropriately selected from soap-free polymerization that does not use an emulsifier and emulsion polymerization that uses an emulsifier. In addition, peroxides, azo compounds, etc. can be used as a radical generating source, and the solubility in the solvent or monomer can be appropriately selected.

[0059] Furthermore, between steps (ii) and (iii), a step (iv) of bonding a silane coupling agent having a polymerizable functional group to the surface of the crosslinked inorganic layer may be included. The method of bonding a silane coupling agent to the surface of the crosslinked inorganic layer is not particularly limited, and can be selected from a method of dispersing particles in a solvent and adding a silane coupling agent, and a method of coating the particle surface with a silane coupling agent. In addition, an acidic or basic aqueous solution serving as a reaction catalyst may be used in combination as necessary.

[0060] In addition, in step (iii), instead of using a monomer having a polyethylene glycol group-containing structural unit, a polymer containing a polyethylene glycol group may be used, and the polyethylene glycol group-containing structural unit may be introduced into the particles by fixation via chemical bonding to the particle surface due to radical chain transfer during polymerization, or by fixation via physical adsorption to the particle surface due to either hydrophobic interaction or electrostatic interaction with the particles, or the entanglement effect with the molecular chains on the particle surface.

[0061] The magnetic particles according to one embodiment of the present invention can be used in an immunoassay device by immobilizing an antibody on the surface of the particles. The antibody is preferably immobilized by physical interaction with the particle surface. EXAMPLES

[0062] The present invention will be described in detail below with reference to the embodiments for carrying out the present invention. However, these are merely examples for explaining the present invention, and are not intended to limit the present invention to the following contents. Furthermore, the present invention can be practiced with appropriate modifications within the scope of the gist of the present invention. Unless otherwise specified, commercially available reagents were used. [Evaluation of iron ion elution] 10 mg of magnetic particles were added to 1 mL of pH 3.5 citrate buffer and stirred for 17 hours at 37° C. The solution from which the particles had been removed was used as the measurement sample, and the amount of leached iron ions was evaluated by measuring the absorbance of the solution at a wavelength of 460 nm. ○: Absorbance 0.02 or less ×: absorbance exceeds 0.02 [Evaluation of immunoassay sensitivity] Preparation of diluted solid phase suspension and labeled antibody solution for detection Anti-PSA antibody was added to magnetic particles dispersed in phosphate buffer (pH 7.5), and the mixture was incubated at 37°C for 3.5 hours to bind the anti-PSA antibody to the magnetic particles. Next, Tris-HCl buffer (pH 8.0) containing polyethylene glycol as a non-specific adsorption inhibitor was added, and the mixture was incubated at 37°C for 17 hours to block the magnetic particles, resulting in anti-PSA antibody-immobilized magnetic particles (F). (F) was further diluted with Tris-HCl buffer (pH 8.0) containing 5% BSA to prepare a diluted solid phase suspension (G). The conjugate of anti-PSA antibody and alkaline phosphatase was also diluted with Tris-HCl buffer (pH 8.0) containing 5% BSA to prepare a labeled antibody solution for detection (H). -Preparation of samples for sensitivity evaluation A phosphate buffer solution (pH 7.1) containing 5% BSA (I) and a sample in which PSA was added to a phosphate buffer solution (pH 7.1) containing 5% BSA (J) were prepared. Sensitivity evaluation Sensitivity was evaluated using a measurement reagent (a lyophilized product containing a diluted solid phase suspension (G) and a labeled antibody solution for detection (H)).

[0063] The sensitivity evaluation sample was measured according to the following procedure.

[0064] The lyophilized diluted solid suspension (G) was dissolved in pure water containing Triton X-100 and the sensitivity evaluation sample (I) or (J), and then subjected to an immunoreaction at 37°C for 5 minutes to perform the first B / F separation. Next, a detection labeled antibody solution (H) dissolved in pure water containing Triton X-100 was added and subjected to an immunoreaction at 37°C for 3 minutes to perform the second B / F separation. Then, a chemiluminescent substrate for alkaline phosphatase (DIFURAT, 3-(5-tert-butyl-4,4-dimethyl-2,6,7-trioxabicyclo[3,2,0]hept-1-yl)phenyl phosphate disodium salt) and a chemiluminescent auxiliary reagent containing fluorescein were added, and the luminescence intensity (count / sec (cps)) was measured.

[0065] The sensitivity was calculated by dividing the count value when measuring (J) by the count value when measuring (I). The higher the value, the higher the sensitivity. ○: Sensitivity 2000 or higher ×: Sensitivity less than 2000 [Example 1] Step (i) (Preparation of magnetized fine particles) 1 g of polydivinylbenzene particles (particle diameter 2.2 μm) was dispersed in 50 mL of 0.1 M sodium chloride pure water at room temperature at a rotation speed of 100 rpm. 1.2 g of a magnetic material (material: magnetite, particle diameter: 10 nm, product name: EMG607, manufactured by Ferrotec Corporation) having a cationic dispersant on the surface was added to this particle dispersion liquid, and the reaction was carried out at room temperature at a rotation speed of 100 rpm for 2 hours. The mixture was washed with pure water and further dried at 50°C for 15 hours to obtain 2.18 g of magnetized particles. The magnetized particles were placed in a hybridization system NHS-0 (manufactured by Nara Machinery Co., Ltd.) and rotated at a speed of 11,300 min. -1 The treatment was performed for 5 minutes at an average temperature of 35°C.

[0066] Step (ii) (Silica Coating on Magnetized Particles) 1 g of the magnetized microparticles was dispersed in 10 mL of 2-propanol, 0.4 g of tetraethyl orthosilicate was added, and the mixture was stirred at room temperature at 180 rpm. 0.4 mL of 25% aqueous ammonia was added, and the mixture was reacted at 60°C and 180 rpm for 4 hours. The mixture was washed with methanol and dried under reduced pressure. The thickness of the silica layer confirmed by a transmission electron microscope was about 5 nm.

[0067] Step (iv) (Introduction of methacryl groups into silica-coated particles) 1 g of the silica-coated particles was dispersed in 10 mL of 2-propanol, 0.5 g of 3-methacryloxypropyltrimethoxysilane and 0.35 mL of 25% aqueous ammonia were added, and the mixture was reacted at 60° C. and 180 rpm for 3 hours. The mixture was washed with methanol and dried under reduced pressure.

[0068] Step (iii) (Polymer Coating on Methacrylic Group-Introduced Particles) 1 g of the particles having methacrylic groups introduced therein was dispersed in 10 mL of pure water in which 0.3 g of polyoxyethylene (23) lauryl ether had been dissolved, and 0.02 g of methacrylic acid, 0.05 g of cyclohexyl methacrylate, and 0.005 g of NOF Corp.'s product name "Perbutyl O" were added, and the mixture was stirred at room temperature at 180 rpm for 1 hour, degassed, and then reacted at 80° C. for 2 hours under a nitrogen atmosphere. The mixture was washed with pure water and methanol, and dried under reduced pressure. (Evaluation Results) The magnetic particles produced had low iron ion elution, with an absorbance of 0.003, and an immunoassay sensitivity of 3785, demonstrating excellent immunoassay sensitivity. [Example 2] Magnetic particles were prepared in the same manner as in Example 1, except that polyoxyethylene (20) cetyl ether was used instead of polyoxyethylene (23) lauryl ether in step (iii) of Example 1. (Evaluation Results) The magnetic particles produced had low iron ion elution, with an absorbance of 0.004, and an immunoassay sensitivity of 3841, demonstrating excellent immunoassay sensitivity. [Example 3] Magnetic particles were prepared in the same manner as in Example 1, except that polyoxyethylene (47) lauryl ether was used instead of polyoxyethylene (20) lauryl ether in step (iii) of Example 1. (Evaluation Results) The magnetic particles produced had low iron ion elution, with an absorbance of 0.003, and an immunoassay sensitivity of 4123, demonstrating excellent immunoassay sensitivity. [Example 4] Magnetic particles were prepared in the same manner as in Example 1, except that a mixture of 0.15 g of polyoxyethylene (47) lauryl ether and 0.15 g of sodium lauryl sulfate was used instead of 0.3 g of polyoxyethylene (20) lauryl ether in step (iii) of Example 1. (Evaluation Results) The magnetic particles produced had low iron ion elution, with an absorbance of 0.001. The immunoassay sensitivity was 7156, demonstrating excellent immunoassay sensitivity. [Example 5] Magnetic particles were prepared in the same manner as in Example 3, except that butyl methacrylate was used instead of cyclohexyl methacrylate in the step (iii) of Example 3. (Evaluation Results) The magnetic particles produced had a low iron ion elution rate with an absorbance of 0.002, and the immunoassay sensitivity was 5728, demonstrating excellent immunoassay sensitivity. [Example 6] Magnetic particles were prepared in the same manner as in Example 3, except that benzyl methacrylate was used instead of cyclohexyl methacrylate in step (iii) of Example 3. (Evaluation Results) The magnetic particles produced had low iron ion elution, with an absorbance of 0.001. The immunoassay sensitivity was 6080, demonstrating excellent immunoassay sensitivity. [Example 7] Magnetic particles were prepared in the same manner as in Example 3, except that styrene was used instead of cyclohexyl methacrylate in step (iii) of Example 3, and 0.08 g of methacrylic acid was used instead of 0.02 g of methacrylic acid. (Evaluation Results) The magnetic particles produced had low iron ion elution, with an absorbance of 0.003, and an immunoassay sensitivity of 3996, demonstrating excellent immunoassay sensitivity. [Comparative Example 1] Magnetic particles containing no silica were prepared in the following manner.

[0069] Step (i) (Preparation of magnetized fine particles) It was prepared in the same manner as in Example 1.

[0070] Step (iv) (Introduction of methacryl groups into silica-coated particles) Methacrylic groups were introduced in the same manner as in Example 1, except that the particles not coated with silica obtained in the above step (i) were used.

[0071] Step (iii) (Polymer Coating on Methacrylic Group-Introduced Particles) 1 g of the particles with the methacryl group introduced therein was dispersed in 10 mL of pure water in which 0.3 g of polyoxyethylene (47) lauryl ether had been dissolved, and 0.05 g of acrylic acid, 0.05 g of styrene, and 0.005 g of NOF Corp.'s product name "Perbutyl O" were added, and the mixture was stirred at room temperature at 180 rpm for 1 hour, degassed, and then reacted in a nitrogen atmosphere at 80° C. for 2 hours. The mixture was washed with pure water and methanol, and dried under reduced pressure. (Evaluation Results) The magnetic particles produced had a high leaching rate of iron ions and were poor in sensitivity for immunoassay. [Comparative Example 2] Particles were prepared in the same manner as in Example 1, except that sodium 1-butanesulfonate was used instead of polyoxyethylene (23) lauryl ether in the step (iii) of Example 1. (Evaluation Results) The magnetic particles produced also provided poor sensitivity for immunoassays. [Comparative Example 3] Particles were prepared in the same manner as in Example 1, except that polyoxyethylene (5) docosyl ether was used instead of polyoxyethylene (23) lauryl ether in the step (iii) of Example 1. (Evaluation Results) The magnetic particles produced had poor sensitivity for immunoassay. [Comparative Example 4] Particles were prepared in the same manner as in Example 1, except that polyoxyethylene (20) docosyl ether was used instead of polyoxyethylene (23) lauryl ether in the step (iii) of Example 1. (Evaluation Results) The magnetic particles produced had poor sensitivity for immunoassay. [Comparative Example 5] Particles were prepared in the same manner as in Example 1, except that polyoxyethylene (30) docosyl ether was used instead of polyoxyethylene (23) lauryl ether in the step (iii) of Example 1. (Evaluation Results) The magnetic particles produced had poor sensitivity for immunoassay.

[0072] [Table 1] [Explanation of symbols]

[0073] 1. Core Particle 2 Nanomagnetic materials 3 Crosslinked inorganic layer 4 Polymer Layer

Claims

1. A magnetic particle having a core particle, a first coating layer formed on a surface of the core particle, and a second coating layer formed on a surface of the first coating layer, the first coating layer is a crosslinked inorganic layer containing nanomagnetic material; The magnetic particles, wherein the second coating layer is a polymer layer having polyoxyethylene alkyl ether having a long-chain alkyl group having 5 to 20 carbon atoms.

2. 2. The magnetic particle according to claim 1, wherein the first coating layer has at least two layers: a nanomagnetic layer and a crosslinked inorganic layer formed on the surface of the nanomagnetic layer.

3. 3. The magnetic particle according to claim 1, wherein the polymer has a monomer unit having a hydrophobic group having 1 to 20 carbon atoms on a side chain.

4. 4. The magnetic particle according to claim 1, wherein the polymer has a monomer unit having a carboxyl group on the side chain.

5. 5. The magnetic particle according to claim 1, wherein the cross-linked inorganic layer of the first coating layer contains silica.

6. Specific surface area is 2 to 100 m 2 The magnetic particles according to any one of claims 1 to 5, wherein the molecular weight is 1 / g.

7. A method for producing magnetic particles according to any one of claims 1 to 6, comprising the following steps (i) to (iii): (i) A step of physically adsorbing a nanomagnetic material onto the surface of a core particle (ii) forming a cross-linked inorganic layer on the surface of the particles to which the nanomagnetic material is adsorbed; (iii) A step of dispersing the particles having the crosslinked inorganic layer formed thereon in an aqueous solution, and forming a polymer layer on the surface of the particles by free radical polymerization of a monomer in the aqueous solution in the presence of a surfactant having a long-chain alkyl group having 5 to 20 carbon atoms.

8. 8. The method for producing magnetic particles according to claim 7, wherein step (i) comprises a step of electrostatically adsorbing a nanomagnetic material to a core particle in an aqueous solution, followed by drying.

9. 9. The method for producing magnetic particles according to claim 7 or 8, characterized in that step (i) comprises a step of dispersing magnetic particles in a high-velocity air stream and dry-modifying the surfaces thereof by impact forces between the particles.

Citation Information

Patent Citations

  • Method for producing magnetic fine particle

    JP2016184703A

  • Composite particles, aqueous coating composition and method for producing the same and coating film

    JP2020084117A

  • Magnetic particles and immunoassay using them

    JP2979414B2

  • Method for producing particles for diagnostic reagents

    JP3738847B2

  • Magnetic particles and fabrication method thereof

    US20090017518A1